Treatment outcomes of injectable thermosensitive hydrogel containing bevacizumab in intervertebral disc degeneration - Chen, Qian; Wang, Juehan; Xia, Qinghong; Wu, Lei; Chen, Fei; Li, Li; Zhu, Ce; He, Miaomiao; Jiang, Yulin; Huang, Yong; Ding, Hong; Wu, Ruibang; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Intervertebral disc (IVD) degeneration (IDD) is a common musculoskeletal condition and its treatment remains a clinical challenge. A decrease in the number of cells and degeneration of the extracellular matrix (ECM) of the nucleus pulposus (NP) are characteristic of disc degeneration. The aim of this study is to investigate the therapeutic potential of bevacizumab, a vascular endothelial growth factor (VEGF) inhibitor, in improving IVD degeneration. High expression of VEGF was observed in degenerating human and rat intervertebral discs. We demonstrated that bevacizumab inhibited the expression of VEGF and MMP3, which promoted the synthesis of COLII and prevented the degeneration of myeloid cells. These results are consistent with the use of a controlled-release injectable thermosensitive hydrogel of bevacizumab to impede VEGF activity in a puncture-induced rat model. Thus, these findings provide evidence that the FDA-approved drug bevacizumab attenuates IDD by inhibiting VEGF expression in rats, implying that bevacizumab delivery via injectable thermosensitive hydrogel is a potential therapeutic strategy for the treatment of IVD degeneration.